Arginine stimulates intestinal cell migration through a focal adhesion kinase dependent mechanism. Issue 4 (11th March 2004) - Rhoads, J M; Chen, W; Gookin, J; Wu, G Y; Fu, Q; Blikslager, A T; Rippe, R A; Argenzio, R A; Cance, W G; Weaver, E M; Romer, L H
Abstract : Background: l -Arginine is a nutritional supplement that may be useful for promoting intestinal repair. Arginine is metabolised by the oxidative deiminase pathway to form nitric oxide (NO) and by the arginase pathway to yield ornithine and polyamines. Aims: To determine if arginine stimulates restitution via activation of NO synthesis and/or polyamine synthesis. Methods: We determined the effects of arginine on cultured intestinal cell migration, NO production, polyamine levels, and activation of focal adhesion kinase, a key mediator of cell migration. Results: Arginine increased the rate of cell migration in a dose dependent biphasic manner, and was additive with bovine serum concentrate (BSC). Arginine and an NO donor activated focal adhesion kinase (a tyrosine kinase which localises to cell matrix contacts and mediates β1 integrin signalling) after wounding. Arginine stimulated cell migration was dependent on focal adhesion kinase (FAK) signalling, as demonstrated using adenovirus mediated transfection with a kinase negative mutant of FAK. Arginine stimulated migration was dependent on NO production and was blocked by NO synthase inhibitors. Arginine dependent migration required synthesis of polyamines but elevating extracellular arginine concentration above 0.4 mM did not enhance cellular polyamine levels. Conclusions: These results showed that l -arginine stimulates cell migration through NO and FAK dependent pathways and that combination therapy with arginine and BSC may enhance intestinal restitution via separate and convergent pathways.